Analisis Keberadaan UMKM Pengrajin Tahu-Tempe dan Potensi Peningkatan Perekonomian Masyarakat (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Micro, small and medium enterprises (MSMEs) have a very vital role in economic growth and development, not only in developing countries but also in developed countries. MSMEs in Indonesia are expected to continue to play an optimal role in the absorption of labor to overcome unemployment. According to BPS data, the number of MSMEs continues to increase and continues to dominate the number of companies. Since the beginning of the New Order era, the Indonesian government has carried out so many programs to encourage the development of MSMEs. On average, MSMEs in Sukouoso Hamlet, Keputon Village, Batang Regency are Tofu-Temple craftsmen and are felt to have potential in improving the community's economy. The formulation of the research problem is: 1. How is the potential of Tofu-Tempe SMEs to improve the community's economy. 2. How is the contribution of the Tofu-Tempe SMEs to the improvement of the community's economy. The purpose of this study was to determine the potential and contribution of SMEs to improving family welfare. This type of research is qualitative with descriptive analytical research. As for the data collection techniques emphasized on observation and interviews. In this method of data analysis used is data reduction, data display, inspection techniques. Various MSMEs in Sukoyoso Hamlet, Keputon Village, Batang Regency have the potential to continue to develop and advance their business actors and the region. The Tofu-Tempe MSMEs also contributed greatly to improving the welfare of the families of the Tofu-Tempe MSMEs in the region. By running the Tofu-Tempe SMEs, it can increase household income, meet the needs of daily life and save money. It can even open up other business opportunities and job opportunities for other people or the surrounding community.